Anti‐GQ1b antibody syndrome: anti‐ganglioside complex reactivity determines clinical spectrum. (14th July 2015) - Fukami, Y.; Wong, A. H. Y.; Funakoshi, K.; Safri, A.Y.; Shahrizaila, N.; Yuki, N.
Abstract : Background and purpose: Anti‐GQ1b antibodies have been found in patients with Miller Fisher syndrome as well as its related conditions. Our aim was to identify the mechanism by which autoantibodies produce various clinical presentations in 'anti‐GQ1b antibody syndrome'. Methods: Immunoglobulin G antibodies to ganglioside complex (GSC) of GQ1b or GT1a with GM1, GD1a, GD1b or GT1b were tested in sera from patients with anti‐GQ1b ( n = 708) or anti‐GT1a ( n = 696) IgG antibodies. Optical densities of the single anti‐GQ1b or anti‐GT1a antibodies were used as reference (100%), and those of anti‐GSC antibodies were expressed in percentages to reference. The relationships between anti‐GSC antibody reactivity and the corresponding clinical features were assessed by multivariate logistic regression analysis. Results: Ophthalmoplegia and hypersomnolence were significantly associated with complex‐attenuated anti‐GQ1b and anti‐GT1a antibodies. Ataxia was associated with GD1b‐ and GT1b‐enhanced anti‐GQ1b antibodies or GM1‐enhanced anti‐GT1a antibodies. Bulbar palsy was associated with GT1b‐enhanced anti‐GQ1b antibodies. Neck weakness was associated with GD1a‐enhanced anti‐GQ1b antibodies. Arm weakness was associated with GD1b‐enhanced anti‐GQ1b and GD1a‐enhanced anti‐GT1a antibodies. Leg weakness was associated with GD1a‐enhanced anti‐GQ1b and anti‐GT1a antibodies. Conclusions: Differences in fine specificity of anti‐GQ1b antibodies are associated with clinical features, possibly due to the different expression of gangliosides in different parts of the nervous system. Abstract : Clickhere to view the accompanying paper in this issue.